2016
DOI: 10.1021/acs.est.5b05870
|View full text |Cite
|
Sign up to set email alerts
|

Smarter Stormwater Systems

Abstract: Existing stormwater systems require significant investments to meet challenges imposed by climate change, rapid urbanization, and evolving regulations. There is an unprecedented opportunity to improve urban water quality by equipping stormwater systems with low-cost sensors and controllers. This will transform their operation from static to adaptive, permitting them to be instantly "redesigned" to respond to individual storms and evolving land uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
123
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(140 citation statements)
references
References 38 publications
(53 reference statements)
0
123
0
1
Order By: Relevance
“…For example, previous studies found that a CMAC retrofit of an existing stormwater detention facility would be approximately three times lower in cost than the equivalent passive alternative based on whole life cycle costs [18], but the scalability of these savings is still unclear. Previous research has identified that one of the biggest foreseeable challenges to advancing the state of the CMAC practice will be to apply systems thinking to understanding the complex spatiotemporal dynamics that govern water flow and quality across large urban areas-i.e., benefits achieved at a local scale may be masked or eliminated at the city scale if the performance of an individual element is not designed in a broader systems context [9]. Regional implementation of many distributed CMAC systems will require potentially complex and careful logic implementation to ensure that that unintended consequences are minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous studies found that a CMAC retrofit of an existing stormwater detention facility would be approximately three times lower in cost than the equivalent passive alternative based on whole life cycle costs [18], but the scalability of these savings is still unclear. Previous research has identified that one of the biggest foreseeable challenges to advancing the state of the CMAC practice will be to apply systems thinking to understanding the complex spatiotemporal dynamics that govern water flow and quality across large urban areas-i.e., benefits achieved at a local scale may be masked or eliminated at the city scale if the performance of an individual element is not designed in a broader systems context [9]. Regional implementation of many distributed CMAC systems will require potentially complex and careful logic implementation to ensure that that unintended consequences are minimized.…”
Section: Discussionmentioning
confidence: 99%
“…A controlled basin in Pflugerville, Texas, achieved a 6-fold reduction in nitrate plus nitrite-nitrogen compared to the same pre-retrofit dry basin (0.66-0.11 mg/L) by extending detention time and releasing water before a storm to create additional storage [7]. Many other studies and field implementation sites demonstrating similar benefits for a variety of goals (e.g., flood control, wet-weather reduction, water quality) have been performed across the county [4,5,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The development of a new generation of sensors, more accurate, smaller, cheaper to manufacture, and able to transmit the information in almost real time, is a contributing factor to the ubiquity of devices generating data of use for the water industry [59][60][61][62][63]. However, despite having access to a broad range of data sources and technical resources, the water utility sector appears to make very limited use of it for the improvement of water quality and source apportionment.…”
Section: Key Opportunities and Challengesmentioning
confidence: 99%
“…Engineers have historically responded to these problems by expanding and upsizing stormwater control infrastructure [10]. However, larger infrastructure frequently brings adverse side-effects, such as dam-induced disruption of riparian ecosystems [11], and erosive discharges due to overdesigned conveyance infrastructure [1].…”
Section: Introductionmentioning
confidence: 99%
“…Green infrastructure, for instance, uses lowimpact rain gardens, bioswales, and green roofs to condition flashy flows and remove contaminants [14][15][16]. Smart stormwater systems take this idea further by retrofitting static infrastructure with dynamically controlled valves, gates and pumps [1,[17][18][19]. By actuating small, distributed storage basins and conveyance structures in real-time, smart stormwater systems can halt combined sewer overflows [20], mitigate flooding [1], and improve water quality at a fraction of the cost of new construction [1,17].…”
Section: Introductionmentioning
confidence: 99%